Utilization of psychotropic medications in children with FASD: a retrospective review - Michael-Roy R. Durr; Susan Petryk; Mansfield Mela; Andrea DesRoches; Mackenzie Wekerle; Sanjida Newaz (BMC, 2021)
Abstract Background Fetal Alcohol Spectrum Disorder (FASD) is a neurodevelopmental condition resulting from pre-natal alcohol exposure. In Canada, an estimated 1.4-4% of newborns are affected by FASD. FASD is often associated with behavioural comorbidities and many individuals require psychotropic medication. However, to date there are no FASD specific guidelines for prescribing medication. Recently, Mela and colleagues described four behavioural symptom clusters commonly seen in FASD with suggested pharmacologic treatment for each cluster within an algorithm. The primary objective was to compare the proposed treatment algorithm retrospectively to actual treatment in a real-world FASD pediatric practice. The secondary objective was to refine the description of symptom clusters which will be targeted with treatment. Methods We collected the diagnostic and medication history from all patient visits of a Regina Developmental Pediatrician who specializes in FASD diagnosis and medication treatment. Three hundred fifty-four FASD patients were identified between 2005 to 2020. The medications that would be predicted from the algorithm were compared to the real-world historical data. A positive case was defined as all algorithm-predicted medications matching the historical data; a negative case had one or more medications failing to match. Results Of the 354 patients, 36 were removed for insufficient information. Of the remaining 318 cases, 172 (54.1%) were positive compared to 146 (45.9%) negatives. In single prescription cases (n=147), the incidence of positives was 67.3%; in multi-prescriptions (n=72) it was 27.8%; and in cases where no prescription was needed (n=99), the positive incidence was 53.5%. Conclusions The prescription algorithm is promising but requires further refinement to accommodate the range of presentations in children with FASD. With respect to unclassified symptoms, we propose the following: sleep onset difficulty as hyperarousal; gender dysphoria and obsessive compulsive disorder as cognitive inflexibility; grief as emotional regulation; and autism spectrum disorder as hyperactive/neurocognitive.